Penerapan Artificial Intelligent Rough Set dalam Pengawasan Kinerja Notaris - Adek Putri; Sarjon Defit; S Sumijan (Rektorat Universitas Putra Indonesia YPTK Padang, 2019)
The Regional Supervisory Council (MPD) has the authority to conduct periodic checks on notaries. In carrying out supervision there is no clear legal or regulatory basis on how the notary performance assessment is categorized as very good, good or bad so there is no common perception from MPD members. The purpose of this study is to help MPD find the assessment category in monitoring the performance of the notary public in West Sumatra. To get the assessment category, the Rough Set method can be used to analyze the performance of a notary public. The data used in this study is the data notary examination at the Regional Office of the Ministry of Law and Human Rights in West Sumatra. This study produced 18 rules to get a decision whether the results of the notary performance check are very good, good or not good. So this research is very appropriate to be applied to get the results of the examination of notary performance.